Effect of specimen size, compressibility and inertia on the response of rigid polymer foams subjected to high velocity direct impact loading. (December 2016) - Koohbor, Behrad; Kidane, Addis; Lu, Wei-Yang
Highlights: Viscoplastic constitutive response of foam at different strain rates from a single test. Effects of specimen aspect ratio on direct impact response of rigid polymer foam. Full-field response of rigid polymer via 3D digital image correlation. High degrees of spatial variability in stress, strain and strain rate. Effect of inertia and compressibility on the dynamic response of rigid foam. Abstract: The influences of specimen length-to-diameter ratio, material compressibility, and inertia on direct impact response of high density closed-cell polymeric foam are investigated. High speed photography and stereovision digital image correlation are conducted to measure the full-field deformation response of the material subjected to direct impact. Inertia stress developed in the specimen is calculated from the acceleration distribution obtained from full-field measurements. Total axial stress magnitude along the axis of the specimen is then reconstructed from inertia and boundary-measured stresses. It is clearly shown that there is an appreciable degree of spatial variability in strains, strain rates and stresses developed in the impacted foam specimens, whereas the degree of such axial variability is more significant at higher length-to-diameter ratios. The study is further extended to take advantage of such spatial variability to identify the rate sensitivity of the examined material over a wide range of strain rates from 1000 s −1 to 5000 s −1 . The approach proposed here is shown to facilitate the identification of viscoplastic constitutive response of low impedance materials using a minimum number of experiments.